MORBIDITIES AFTER LOCAL/REGIONAL TREATMENT OF BREAST CANCER AND PATIENTS’ QUALITY OF LIFE - Beyza Özçınar; Sertaç Ata Güler; Vahit Özmen; Bahadır M. Güllüoğlu; Nazmiye Kocaman; Mine Özkan; Gülay Sarıçam; Mahmut E. Müslümanoğlu; Abdullah İğci; Mustafa Keçer (European Journal of Breast Health, 2010)

(untitled)
Introduction:The aim of this prospective clinical study was to evaluate early and late complications of diff erent surgical procedures, and compare conservative surgeries (breast conserving surgery, sentinel lymph node biopsy) to more radical surgical treatments (mastectomy, axillary lymph node dissection), and fi nd factors related to these complications in patients with early breast cancer.Materials and Methods:218 early stage breast cancer patients (stage I and II) were enrolled in this prospective study. We studied physical complications (restrictions in shoulder motions, shoulder functional capacity, pain, lymphedema and sensory loss), psychological complications (depression, decreased quality of life) and the factors related to these complications in patients after breast surgery and/or radiotherapy at fi rst week, at 9th-12th months and at mean follow up time of 50 months.Results:Median age of 218 patients was 48 (19-82) years. Lymphedema rates after surgery were 14.7 %, 24.8% and 6.9% at fi rst week, 9th-12th months, and long term respectively. In early postoperative period, pain and functional capacity of the effected shoulder were worse than preoperatively measured values and all the motions of shoulder were eff ected signifi cantly. On the other hand, at 9th-12th months, only internal fl exion motion was still aff ected. At long term period, all shoulder motions, pain and functional capacitiy were in normal ranges like before treatment. The factors related with lymphedema were axillary lymph node dissection (p=0.002), radiation therapy to axillae (p<0.001), and axillary drainage (p=0.005). The factors related to postoperative depression at early period were cigarette smoking (p=0.008), axillary lymph node dissection (p=0.045) and arm lymphedema (p=0.005), also at long term period were axillary lymph node dissection (p=0.021), mastectomy (p=0.036), drain usage (p=0.028) and sensory loss (p=0.027).Discussions:After local treatment of breast cancer (surgery and/or radiotherapy), more than a half of the patients were eff ected at least one of these complications: pain, restrictions in shoulder motions and functional capacity of shoulder, lymphedema, sensory loss, hardness at arm. The patients who had sentinel lymph node biopsy, axillary dissection without axillary radiotherapy had better quality of life.